Monocyte-Derived Macrophages Are Impaired in Myelodysplastic Syndrome - Yu Han; Huaquan Wang; Zonghong Shao (Journal of Immunology Research)
Background. The myelodysplastic syndrome (MDS) comprises a group of clonal hematopoietic stem cell diseases characterized by cytopenia, dysplasia in one or more of the major myeloid lineages, ineffective hematopoiesis, and increased risk of development of acute myeloid leukemia (AML). Macrophages are innate immune cells that ingest and degrade abnormal cells, debris, and foreign material and orchestrate inflammatory processes. We analyzed the role of macrophages from MDS patients in vitro. Methods. Macrophages were induced from peripheral blood of patients with MDS via granulocyte macrophage colony-stimulating factor (GM-CSF). Phagocytic capacity of macrophages was measured with carboxyfluorescein succinimidyl ester and fluorescent microspheres. CD206 and signal regulatory protein alpha (SIRPα) on macrophages were detected by flow cytometry. Inducible nitric oxide synthase (iNOS) was measured by ELISA method. Results. Compared with normal control group, the number of monocytes increased in MDS patients. However, the monocytes showed impaired ability to induce macrophages and the number of macrophages induced from MDS samples was lower. Further, we demonstrated that the ex vivo phagocytic function of macrophages from MDS patients was impaired and levels of reorganization receptors CD206 and SIRPα were lower. Levels of iNOS secreted by macrophages in MDS were increased. Conclusions. Monocyte-derived macrophages are impaired in myelodysplastic syndromes.